Do you know Dewey? : exploring the Dewey decimal system - Cleary, Brian P., 1959-; Lew-Vriethoff, Joanne (Minneapolis, MN : Millbrook Press, 2013)
Introduces readers to the Dewey decimal system.
5.7
3-6.
3-6
Keywords: Classification, Dewey decimal -- Juvenile literature; Classification, Dewey decimal; Dewey Decimal Classification; Picture books for children